2003
DOI: 10.1200/jco.2003.09.081
|View full text |Cite|
|
Sign up to set email alerts
|

Randomized Trial of Dose-Dense Versus Conventionally Scheduled and Sequential Versus Concurrent Combination Chemotherapy as Postoperative Adjuvant Treatment of Node-Positive Primary Breast Cancer: First Report of Intergroup Trial C9741/Cancer and Leukemia Group B Trial 9741

Abstract: Dose density improves clinical outcomes significantly, despite the lower than expected number of events at this time. Sequential chemotherapy is as effective as concurrent chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
795
4
30

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,432 publications
(859 citation statements)
references
References 12 publications
30
795
4
30
Order By: Relevance
“…As for neurotoxicity, a well-known side effect of docetaxel administration although it may persist after treatment, in the present study, it was found to be very rare. In other studies where paclitaxel was used, neurotoxicity seemed to be more frequent and more severe, particularly when a dose-dense or a weekly schedule was used [13,14]. The present study has several potential limitations.…”
Section: Yes Nomentioning
confidence: 69%
“…As for neurotoxicity, a well-known side effect of docetaxel administration although it may persist after treatment, in the present study, it was found to be very rare. In other studies where paclitaxel was used, neurotoxicity seemed to be more frequent and more severe, particularly when a dose-dense or a weekly schedule was used [13,14]. The present study has several potential limitations.…”
Section: Yes Nomentioning
confidence: 69%
“…intensification, and were predicted to increase the probability of tumour eradication (Norton, 1998(Norton, , 1997(Norton, , 2001). In particular the dose densification strategy was tested in a series of clinical trials by the Cancer and Leukaemia Group B (CALGB) and the American Breast Intergroup (Citron et al, 2002(Citron et al, , 2003. The results supported the theory that dose dense treatment would lead to a significant improvement in clinical outcomes, additionally exemplifying how a mathematical model can make successful predictions for improved chemotherapy protocols (Piccart-Gebhart, 2003).…”
Section: Introductionmentioning
confidence: 88%
“…Preoperative chemotherapy for HER2-negative tumors employed one of the following regimens: AC (six cycles of doxorubicin 60 mg/m 2 and cyclophosphamide 600 mg/m 2 , q 3 weeks); dose dense (dd) AC (AC q 2 weeks with filgrastim) [11]; AD (six cycles of doxorubicin 50 mg/m 2 and docetaxel 75 mg/m 2 ) or DC (six cycles of docetaxel 75 mg/m 2 and capecitabine 2 9 dd 1,000 mg/m 2 orally during 14 days, q 3 weeks) [12,13]. For HER2-positive tumors, the regimens included ddAC and PTC (paclitaxel 80 mg/m 2 week -1 , trastuzumab 2 mg/kg and carboplatin AUC 2-3 mg/ml min times 6, q 8 weeks) after 2005 [14,15].…”
Section: Clinicopathological Datamentioning
confidence: 99%